Physical activity and exercise on diabetic foot related outcomes: A systematic review. (May 2018) - Matos, Monica; Mendes, Romeu; Silva, André B.; Sousa, Nelson
Abstract: Background: Diabetic foot is one of the most common complications of diabetes. It has the potential risk of pathologic consequences including infection, ulceration and amputation, but a growing body of evidence suggests that physical activity and exercise may improve diabetic foot outcomes. Objective: To analyze de effects of exercise and physical activity interventions on diabetic foot outcomes. Methods: A comprehensive and systematic search was conducted according to PRISMA recommendations. Only controlled clinical trials with patients with diabetes were included. Results: Six studies, involving 418 patients with diabetes, were included. Two studies used only aerobic exercise; two studies combined aerobic, resistance and balance exercise; and two studies combined aerobic and balance exercise by Thai Chin Chuan methods. Physical activity and exercise significantly improved nerve velocity conduction, peripheral sensory function and foot peak pressure distribution. Moreover, the ulcers incidence rate per year was lower in the intervention groups, compared with the controls [0.02 vs. 0.12]. Conclusion: This review suggests evidence that physical activity and exercise is an effective non-pharmacological intervention to improve diabetic foot related outcomes. Combined multi-disciplinary treatments are more effective in the prevention of foot complications in patients with diabetes.